Influence of the examination on the functional state of the organism of schoolboys - Nugumanova, Sh.M. (Publ.KarSU, 2018)
The work is devoted to an estimation of influence of the adverse ecological factors on a functional pressure of schoolboys CNS of the at passing an examination. Object of research the pupils of average comprehensive schools of. Karaganda city living in various on an ecological situation areas. Is revealed, that negative ecological conditions of a residence have on different influence on a functional condition and serviceability CNS and intimately — vascular of systems in time of stress situation (passing an examination). There are distinctions to a sexual attribute. High nervous and emotional state, which occurs under the influence of stress factors in extreme conditions can lead to disruption of the mechanisms of homeostasis, and if its effect on the body is high in intensity, there may be a depletion of reserve capabilities organism. The revealed differences in the response of the cardiovascular and central nervous systems in boys and girls suggest a higher «mobilization readiness» of the male body for the effects of stress. The female organism reacts to the exam less pronounced, but more prolonged arousal, which may indicate the involvement of the hormonal system in the body's response to a stressful situation.
Оқушылар ағзасының функционалдық жағдайына емтиханның əсерін бағалау
Оценка влияния экзамена на функциональное состояние организма школьников
Keywords: of influence; ecologia; examination; reaction; organism; process; central nervous system; cardiovascular system; adaptation